2010
DOI: 10.1210/jc.2009-1584
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Different Measures of Obesity for Incident Cardiovascular Events and Mortality

Abstract: WHtR represents the best predictor of cardiovascular risk and mortality, followed by WC and WHR. Our results discourage the use of the BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
325
2
35

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(387 citation statements)
references
References 35 publications
15
325
2
35
Order By: Relevance
“…The association was stronger than BMI, waist‐to‐hip ratio and waist circumference 53. Similar results were found in a study of German patients 54. A meta‐analysis of studies that evaluated different measures of obesity as predictors of cardiovascular events also found that waist‐to‐height ratio was the best predictor of cardiovascular events 55.…”
Section: Alternative Indices Of Obesitysupporting
confidence: 78%
“…The association was stronger than BMI, waist‐to‐hip ratio and waist circumference 53. Similar results were found in a study of German patients 54. A meta‐analysis of studies that evaluated different measures of obesity as predictors of cardiovascular events also found that waist‐to‐height ratio was the best predictor of cardiovascular events 55.…”
Section: Alternative Indices Of Obesitysupporting
confidence: 78%
“…For WHtR, the AUC was 66 % for men and 78 % for women. There are many studies evaluating the predictive power of anthropometric indices for cardiovascular deaths, CVD, hypertension, cardiometabolic risks, diabetes and dyslipidaemia (3,13,(31)(32)(33)(34)(35) . Systemic reviews and metaanalyses have shown that WHtR is superior in estimating cardiometabolic risks.…”
Section: Obesitymentioning
confidence: 99%
“…Measures of abdominal obesity, principally waist circumference and WHR, are used as surrogates of body fat centralization and have been used to evaluate CVD risk (31,32) . Obesity was more strongly related to TAG than other variables in both sexes.…”
Section: Discussionmentioning
confidence: 99%